İçten Yanmalı Motorun Soğutma Sisteminde Soğutucu Akışkan Kullanımının Deneysel İncelenmesi: Ön Çalışma - Kayalı, Yavuz Selim; Yüksel, Tahsin; Kapıcıoğlu, Abdullah (Fırat University, 2025)
İçten yanmalı motorlarda kullanılan soğutma sisteminin olumsuz etkilerini azaltmak ve daha verimli bir sistem oluşturmak amacıyla yeni bir soğutma sistemi tasarlanmıştır. Ön çalışma için kurulan deney düzeneğinde, motor soğutma sisteminde soğutucu akışkan olarak R134a gazı kullanılmıştır. Farklı sıcaklıklarda (50, 60, 70, 80, 90, 100, 110, 120 °C) sabitlenmiş simüle edilmiş silindiri soğutmak için soğutma sistemine doldurulan farklı ağırlıklardaki (400, 450, 500, 550, 600 g) gaz kütlelerinin soğutma etkisi belirlenmiştir. Sistemdeki sıcaklık ve basınç değerleri ölçülerek sistemin ısı transfer katsayısı, akışkan debisi ve ısı transfer hızları hesaplanarak karşılaştırmalar yapılmıştır. Çalışmada kullanılan en verimli akışkan ağırlığı 550 g olarak belirlenmiştir. Sirkülasyon pompası olmayan sistemde, ısı alan ve ısı veren bölümler arasındaki basınç farkı, soğutucu gazın dolaşımına olanak sağlamaktadır. Bu durumun, sıcaklık artışına bağlı olarak ısı transfer katsayısının artmasıyla mümkün olduğu gözlemlenmiştir. Sistemde pompa bulunmaması, motor performansına katkı sağlayacaktır. Soğutucu akışkanın gaz halinde olması, daha küçük motor yapıları, daha düşük araç ağırlığı, daha az yakıt tüketimi ve daha az egzoz emisyonu sağlayacaktır.

A new cooling system has been designed to reduce the adverse effects of the cooling system used in internal combustion engines and to create a more efficient system. R134a gas was used as the refrigerant in the engine cooling system in the experimental setup set up for the preliminary study. The cooling effect of gas masses of different weights (400, 450, 500, 550, 600 g) filled into the cooling system for cooling the simulated cylinder fixed at different temperatures (50, 60, 70, 80, 90, 100, 110, 120 °C) was determined. By measuring the temperature and pressure values in the system, comparisons were made by calculating the heat transfer coefficient, fluid flow rate and heat transfer rates of the system. The most efficient fluid weight used in the study was determined as 550 g. In the system without a circulation pump, the pressure difference between the heat receiving and heat giving sections allows the refrigerant gas to circulate. It has been observed that this situation is made possible by the increase in the heat transfer coefficient depending on the temperature increase. The absence of a pump in the system will contribute to engine performance. Having the refrigerant in gaseous form will enable smaller engine structures, lower vehicle weight, less fuel consumption and less exhaust emissions.
Experimental Investigation of the Use of Refrigerant in the Cooling System of the Internal Combustion Engine: Preliminary Study
Keywords: Heat Transfer in Automotive; Otomotivde Isı Transferi